إبرام الصفقات العمومية عن طريق الإجراءات المكيفة (الاستشارة وسند الطلب) - فيروز بن يحيى - كوثـــــر سليني (جامعة المسيلة, 2021)
يعتبر إجرائي الاستشارة وسند الطلب أحد طرق إبرام الطلبيات عن طريق الصفقات العمومية، حيث نظمها المشرع ضمن القسم الخاص بالإجراءات المكيفة والتي استحدثها المشرع الجزائري في المرسوم 15/247 وذلك بغرض تبسيط إجراءات إبرام الصفقات العمومية التي لا تتجاوز مبالغها الحدود المحددة قانونا للإبرام عن طريق الإجراءات الشكلية من جهة، ومن جهة ثانية حماية للمال العام وترشيد إنفاقه في هذا المجال، حيث ترك المشرع الحرية للهيئات العمومية صلاحيات ومهام تنظيم الإجراءات المكيفة وذلك نظرا لارتباطها بالخدمات ذات النمط العادي والمتكرر، ومع ذلك فإنه تم تسجيل قصور في التنظيم القانوني المحدد للإجراءات المكيفة خاصة فيما يتعلق بمحدودية المنافسة وآليات الرقابة على هذا النوع من الإجراءات، ولعل السبب في ذلك يعود إلى رغبة المشرع الجزائري في الحفاظ على سير المرافق العامة بانتظام واطراد وتقديم الخدمة العامة في مختلف الظروف. Abstract The consultation procedure and the purchase order is one of the ways of concluding orders through public deals, as it was organized by the legislator within the section of the conditioned procedures, which was introduced by the Algerian legislator in the decree 15/247, with the aim of simplifying the procedures for concluding public deals whose amounts do not exceed the legally defined limits by concluding formal procedures from On one hand, on the other hand, the protection of public money and the rationalization of its spending in this field, where the legislator left the freedom to the public bodies the powers and tasks of organizing the adapted procedures, due to their connection with the services of a the regular and recurring pattern. However, a shortcoming was recorded in the specific legal regulation of the adapted procedures, especially with regard to the limitation of competition and the oversight mechanisms of this type of procedure. Perhaps the reason for this is due to the legislator’s desire to maintain the regular functioning of public utilities and to provide public service in various circumstances.
Keywords: إبرام الصفقات العمومية- الإجراءات المكيفة - الاستشارة-سند الطلب)